Counter-Insurgency against ‘kith and kin’?: the British Army in Northern Ireland, 1970–76 - Burke, Edward (Taylor & Francis, 2015)
This article argues that state violence in Northern Ireland during the period 1970–1976—when violence during the Troubles was at its height and before the re-introduction of the policy of police primacy in 1976—was on a greatly reduced scale from that seen in British counterinsurgency campaigns in the colonies after the Second World War. When the army attempted to introduce measures used in the colonies—curfews, internment without trial—these proved to be extremely damaging to London's political aims in Northern Ireland, namely the conciliation of the Catholic minority within the United Kingdom and the defeat of the IRA. However, the insistence by William Whitelaw, secretary of state for Northern Ireland (1972–73), on ‘throttling back'—the release of internees and the imposition of unprecedented restrictions on the use of violence by the army—put a serious strain on civil-military relations in Northern Ireland. The relatively stagnant nature of the conflict—with units taking casualties in the same small ‘patch’ of territory without opportunities for the types of ‘positive actions’ seen in the colonies—led to some deviancy on the part of small infantry units who sought informal, unsanctioned ways of taking revenge upon the local population. Meanwhile, a disbelieving and defensive attitude at senior levels of command in Northern Ireland meant that informal punitive actions against the local population were often not properly investigated during 1970–72, until more thorough civilian and military investigative procedures were put in place. Finally, a separation of ethnic and cultural identity between the soldiers and the local population—despite their being citizens of the same state—became professionally desirable in order for soldiers to carry out difficult, occasionally distasteful work.